Comparisons of catch-up among developed nations and developing countries - Wu, Han; Xiong, Jie; Li, Qian; Wei, Tian (Journal of Eastern European and Central Asian Research (JEECAR), 2018)
Although interest in the catching-up strategy of developing countries has increased during recent years, this line of research is focused on national analysis from the beginning, using developed nations as a benchmark for productive lagging-behind countries, which need to be reviewed. Accordingly, we utilize literature analysis method to distinguish the difference among developing and developed countries of the catching-up process. Based on our analysis, we state that the lagging-behind countries have late-coming advantages. In the short term, the developing countries are able to achieve technical imitation by catching-up with the technology. However, in the long run, imitation innovation is always based on the main concepts of developed countries, and does not really integrate the actual situation and social resources with the economic situation of developing countries. Consequently, it is essential for developing countries to find an innovative way to fulfill the transformation.